2000
DOI: 10.1046/j.1523-5408.2000.00045.x
|View full text |Cite
|
Sign up to set email alerts
|

Rate Your Plate: A Dietary Assessment and Educational Tool for Blood Cholesterol Control

Abstract: Practitioners who wish to deliver targeted nutritional advice to their patients for the prevention and management of elevated serum cholesterol levels must first assess their patients' diets. Unfortunately, many primary care providers do not have sufficient training in nutrition to do this adequately. In this situation, dietary assessment instruments would be useful; however, standard dietary assessment methods such as 24‐h recalls, food records, and food‐frequency questionnaires are inappropriate for use in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 17 publications
(15 reference statements)
0
23
0
Order By: Relevance
“…As a dietary assessment instrument we used the RYP test, a self-administered food-frequency questionnaire whose validity was previously established in calibration studies through correlation coefficients relating RPY score and various measures of dietary fat, saturated fat and cholesterol intake [25], and that was successfully used in a variety of settings and demographic groups [25], [40], [41]. Present findings show that the mean total RPY score in daytime workers was significantly, though slightly, higher than that reported by rotating shift workers; however, multinomial regression analysis reveals that quality of nutrition is not an independent factor in determining the risk for overweight in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…As a dietary assessment instrument we used the RYP test, a self-administered food-frequency questionnaire whose validity was previously established in calibration studies through correlation coefficients relating RPY score and various measures of dietary fat, saturated fat and cholesterol intake [25], and that was successfully used in a variety of settings and demographic groups [25], [40], [41]. Present findings show that the mean total RPY score in daytime workers was significantly, though slightly, higher than that reported by rotating shift workers; however, multinomial regression analysis reveals that quality of nutrition is not an independent factor in determining the risk for overweight in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…The RYP was developed by Gans et al in the late 1980s (periodically updated thereafter) as a paper-based, self-administered assessment tool of the eating-pattern that would allow a quick evaluation of dietary habits related to heart disease prevention [8,9]. This tool has been validated and shown to be an effective part of a program to lower patient’s cholesterol [10].…”
Section: Methodsmentioning
confidence: 99%
“…The LiveWell intervention was conducted as a pilot study that enrolled patients with dyslipidemia who also scored low on a brief food- frequency screening questionnaire (Rate-Your -Plate) [8]. The counseling requires only 5–6 minutes of contact with the provider (in this case the primary care physician), and can be delivered during a regular office visit for dyslipidemia.…”
Section: Introductionmentioning
confidence: 99%
“…This instrument was designed to be completed independently by adolescents and was based on literature review, expert feedback, and feasibility testing, which found it to be feasible in public health and primary care settings, similar to the performance of the longer Food Habits Questionnaire and Rate Your Plate. 19,20 Physical activity was assessed by accelerometer using the ActiGraph Model GT1M for a 7-day period; average daily minutes of light, moderate, and vigorous activity were calculated using published cut points. 21 Sedentary behavior, TV watching and playing computer or video games on an average school day was measured using 2 items from the Youth Risk Behavior Survey (YRBS).…”
Section: At Each Visitmentioning
confidence: 99%